Engineering Bacillus subtilis for production of 3-hydroxypropanoic acid - Garg, Abhroop; Jers, Carsten; Hwang, Hee Jin; Kalantari, Aida; Ventina, Ildze; Mijakovic, Ivan (Frontiers in Bioengineering and Biotechnology, 2023)
3-Hydroxypropionic acid (3-HP) is a valuable platform chemical that is used as a precursor for several higher value-added chemical products. There is an increased interest in development of cell factories as a means for the synthesis of 3-HP and various other platform chemicals. For more than a decade, concentrated effort has been invested by the scientific community towards developing bio-based approaches for the production of 3-HP using primarily Escherichia coli and Klebsiella pneumoniae as production hosts. These hosts however might not be optimal for applications in e.g., food industry due primarily to endotoxin production and the pathogenic origin of particularly the K. pneumoniae. We have previously demonstrated that the generally recognized as safe organism Bacillus subtilis can be engineered to produce 3-HP using glycerol, an abundant by-product of the biodiesel industry, as substrate. For commercial exploitation, there is a need to substantially increase the titer. In the present study, we optimized the bioprocess conditions and further engineered the B. subtilis 3-HP production strain. Thereby, using glycerol as substrate, we were able to improve 3-HP production in a 1-L bioreactor to a final titer of 22.9 g/L 3-HP.